Inhibition of intimal hyperplasia in murine aortic allografts by administration of a small-molecule TLR4 inhibitor TAK-242. Issue 1 (December 2017) - Wu, Chuangyan; Ding, Xiangchao; Zhou, Cheng; Ye, Ping; Sun, Yuan; Wu, Jie; Zhang, Anchen; Huang, Xiaofan; Ren, Lingyun; Wang, Ke; Deng, Peng; Yue, Zhang; et al.
Abstract Graft arteriosclerosis (GA) is the leading cause of late cardiac allograft dysfunction. The innate immune system plays a major role in GA, paprticularly Toll-like receptor 4 (TLR4) signaling. Here we characterized the role of TLR4 and its antagonist TAK-242 in a mouse model of GA. BALB/c (H-2d) donor aortas were transplanted into C57BL/6 (H-2b) recipients, and the mice received intraperitoneal injection of 3 or 10 mg/kg of TAK-242 or vehicle every other day for 1, 2, 4, 6, 8 and 12 weeks. With TAK-242 administration, intimal hyperplasia initially appeared at 2 weeks after transplantation, and TAK-242 postponed the progression of neointimal formation in allogeneic aortic grafts. TAK-242 treatment reduced CD68+ macrophage accumulation in the allografts, reduced the levels of ly-6Chi monocytes in peripheral blood, bone marrow and spleen, and downregulated proinflammatory cytokine and chemokine levels.Ex vivo we observed that TAK-242 could improve the graft microenvironment by interfering the Tck/Mφ IL12p70 and IFNγ axis, reducing CCL2-mediated migration of vascular smooth cells.